Social intelligence and its role in demonstration the Potential abilities for individuals - رشيد, اسيل زهير; سلطان, سندية مروان (Journal of Economics and Administrative Sciences, 2013)
Abstract          The following research is marked by "social intelligence and its role in demonstration the potential abilities for individuals." The discussion dealt with the concepts of contemporary is very important because of their significant role in influencing the work of the Organization, as adopted link between the concepts of social intelligence and the potential role of the first to show the second .The research hypotheses tested in three health institutions in the city of Mosul, the research community is represented (Al-Salam Hospital and General Hospital and the son of ether), while the sample were the leaders of these institutions, twin directors and heads of sections. I suppose research and a relationship with a link and the impact of significant figures between the two variables, and use for the purpose of measuring this issue a number of statistical tools appropriate for the analysis of data obtained from the sample. and finally research found a number of conclusions of the most important of the skills Relational between individuals, which include social understanding and social skills they may have attracted the attention slice wide range of leaders, administrators, which means that most of the administrative leaders embody their social intelligence through these skills. It also recommended research a set of recommendations that enrich the field mentioned the most important of the necessity of understanding the fact that social intelligence is a critical component in building personal leadership and elaborated so as to ensure access to the level of functioning of the administrative leaders and organizations are n of administrative and transition from the administrative level to another. looking to make the level of intelligence of the individual priorities that qualify for the positio